Classical probability density distributions with uncertainty relations for ground states of simple non-relativistic quantum-mechanical systems. (1st November 2016) - Radożycki, Tomasz
ABSTRACT: The probability density distributions for the ground states of certain model systems in quantum mechanics and for their classical counterparts are considered. It is shown that classical distributions are remarkably improved by incorporating into them the Heisenberg uncertainty relation between position and momentum. Even the crude form of this incorporation makes the agreement between classical and quantum distributions unexpectedly good, except for the small area, where classical momenta are large. It is demonstrated that the slight improvement of this form makes the classical distribution very similar to the quantum one in the whole space. The obtained results are much better than those from the WKB method. The paper is devoted to ground states, but the method applies to excited states too. Abstract :